Analysis of The Government’s Role in Implementing Presidential Regulation (PERPRES) Number 72 of 2021 on Accelerating Stunting Reduction in Efforts to Maintain National Resilience - Nefrisa Adlina Maaruf; Irwan Triadi (JURNAL HUKUM SEHASEN, 2023)
The audit and economic consulting firm PricewaterhouseCoopers (PWC) has published a study that predicts Indonesia's economic position could reach the 5th rank globally. This is based on Indonesia entering the demographic bonus era, where the productive-age population exceeds the non-productive age group. The demographic bonus presents a golden opportunity for the economic and social development of Indonesia. However, according to data from the 2022 National Nutrition Status Survey (SSGI), the prevalence of stunting in Indonesia is at 21.6%, just below the WHO standard of 20%. This has caught the government's attention, leading to the issuance of Presidential Regulation of the Republic of Indonesia Number 72 of 2021 on Accelerating Stunting Reduction. It is hoped that the stunting issue in Indonesia will be addressed promptly because stunting not only has the potential to cause future health crises but also poses a barrier to achieving strong national resilience. This research aims to understand the role of the government in implementing Presidential Regulation Number 72 of 2021 on accelerating stunting reduction in efforts to maintain national resilience. This study uses a normative juridical research method, which involves examining literature and secondary data. The research results indicate that it will be challenging to maintain national sovereignty if the future generation of the nation experiences low learning ability and is at risk of chronic diseases such as diabetes, hypertension, and obesity due to poor nutrition or stunting.